A framework for enhancing government service delivery using mobile technologies: an African countries context - Ogunleye, Olalekan Samuel (Department of Information Systems, 2017)
Electronic government (e-government) is how the providers of public services interact with the citizen and business via electronic means. The internet is the most commonly used electronic channel. E-government can provide major benefits to citizens and businesses by making the delivery of public services more efficient and effective. However, recent advances in mobile technology have offered the potential to support government services at various levels. This has made it possible to deliver services to the citizens who have no convenient physical access to government services, for example, people living in rural areas and those who are continually on the move, such as business professionals. This study explores the possibilities of effectiveness, resistance, opportunities and issues related to supporting government services delivery through using mobile cellular technologies. This research study focused on the South African and Nigerian contexts. The focus was to explore various ways that the government can use mobile technologies to improve the provision of government services. A major output of this research work is a conceptual framework to guide mobile government implementation as a vehicle for delivery of government services. Literature from both academic and professional domains were consulted throughout the study. Furthermore, a case study research was conducted in two organisations, which are different in terms of cultural and transformative settings (one in South Africa and another in Nigeria). The study followed an interpretive research approach, and collected data through semi-structured interviews in the two organizations. The data gathered were relevant to the implementation of m-government systems. The study relied on two underpinning theoretical frameworks, namely Structuration Theory and Actor Network Theory to understand the socio-technical factors affecting the implementation of m-government systems in government organisations. The perspective of duality of structure and moments of translation from both Structuration Theory and Actor Network Theory were adopted to analyse the data collected in the case study organisations.